2009
DOI: 10.1590/s0102-311x2009001200008
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade dos dados relativos ao cumprimento da Emenda Constitucional nº. 29 declarados ao Sistema de Informações sobre Orçamentos Públicos em Saúde pelos municípios de Pernambuco, Brasil

Abstract: O estudo analisa a confiabilidade dos dados relativos ao cumprimento da Emenda Constitucional nº. 29 (EC29) declarados ao Sistema de Informações sobre Orçamentos Públicos em Saúde (SIOPS) pelos municípios de Pernambuco, Brasil. Configura-se como um estudo quantitativo, do tipo transversal e de caráter analítico, tendo como referência o período de 2000 a 2005. Os demonstrativos contábeis auditados pelo Tribunal de Contas do Estado (TCE) foram tomados como parâmetro para verificar a confiabilidade dos percentuai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
23

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 5 publications
0
2
0
23
Order By: Relevance
“…With reference to the Sipos indicator, Lima et al 42 affirm that trustworthy information is being used. However, Gonçalves et al 43 identified problems relating to the uniformity between the register of the Siops data and the Financial Auditing Court for the State of Pernambuco. Based on these, the authors reinforce the need for studies that investigate the trustworthiness of the system 29,31 .…”
Section: Discussionmentioning
confidence: 99%
“…With reference to the Sipos indicator, Lima et al 42 affirm that trustworthy information is being used. However, Gonçalves et al 43 identified problems relating to the uniformity between the register of the Siops data and the Financial Auditing Court for the State of Pernambuco. Based on these, the authors reinforce the need for studies that investigate the trustworthiness of the system 29,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Teixeira e Teixeira (2003), aos poucos esse sistema garantiu o acompanhamento do processo de avaliação do desempenho dos sistemas de saúde, além de tornar-se instrumento para verificação do cumprimento da EC n o 29/2000 (Gonçalves et al, 2009).…”
Section: Discussionunclassified
“…Com os desafios introduzidos pelo SUS no âmbito do financiamento, essas informações são imprescindíveis. Nessa perspectiva, pode-se afirmar que, com o aprimoramento do Siops, se conferiu maior acessibilidade e visibilidade aos dados financeiros de estados e municípios (Gonçalves et al, 2009).…”
Section: Discussionunclassified
“…The Health Reform movement resulted in the establishment of the Unified Health System (SUS) by the 1988 Federal Constitution and, twenty-eight years later, its funding remains unclear [1][2][3][4][5][6][7][8][9][10] . We can say that most of the structural problems that plague the SUS today are related to funding 5,7,8,11,12 .…”
Section: Introductionmentioning
confidence: 99%